The Boundedness of Marcinkiewicz Integrals Associated with Schrödinger Operator on Morrey Spaces - Dongxiang Chen; Fangting Jin (Journal of Function Spaces)
Let L=-Δ+V be a Schrödinger operator, where V belongs to some reverse Hölder class. The authors establish the boundedness of Marcinkiewicz integrals associated with Schrödinger operators and their commutators on Morrey spaces.